The Effect of Critical Reading Skill on Academic Success in Social Studies - Ozensoy, Ahmet Utku (ANI YAYINCILIK, 2021)
Purpose: The research aims to investigate the effect of critical reading skill teaching on students' academic success in social studies course. Method: Experimental model was used in the research. The "pre-test post-test control group pattern" of this model was preferred. In the experimental process, the effect of teaching based on critical reading skill in the social studies course on students' academic success was investigated. The experimental process was carried out between April and May 2018 in a secondary school (6th grade students) in the central district of Mus. Experiment and control groups of the research were randomly assigned. In the study, an academic success test was applied to the experiment and control groups as pre-test and post-test. The data were analysed by covariance analysis. Findings: In the research, there was a significant difference between the post-test score averages of the experiment and control groups favouring the experiment group. This finding reveals that teaching critical reading skill is effective in increasing students' academic success. Implications for Research and Practice: In the research, it was found that when the social studies course was conducted according to critical reading skills, it increased students' academic success. Therefore, the teaching of critical reading skill should be given importance in the social studies course. Social studies teachers should receive in-service training on critical reading. Critical reading should be used effectively in courses. Researches should be done on the effect of critical reading skill on other skills. (C) 2020 Ani Publishing Ltd. All rights reserved
Keywords: Social studies; Social studies teaching; Skill teaching; Critical reading